2005
DOI: 10.1590/s0103-64402005000300008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the retention of zirconia-based ceramic posts luted with glass ionomer and resin cements

Abstract: The retention of zirconia-based ceramic posts (CosmoPost system) luted with glass ionomer and resin cements was evaluated. Thirtytwo extracted, caries-free, unrestored teeth were selected and stored in chlorhexidine and water solution. The teeth were endodontically treated and randomly assigned to two groups (n=16). Each tooth was decoronated and prepared to a depth of 10.0 mm from root surface to receive a 1.4 mm diameter zirconium dioxide post. Each group had posts cemented with either glass ionomer cement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
2
10
1
1
Order By: Relevance
“…With regard to the reduction in bond strength values when push-out testing was used, it was caused by internal stresses at the dentin-post interface 72) . On the influence of luting agents upon retentive strength, Table 3 also shows that zirconia posts bonded to teeth with resin cements exhibited higher retentive strengths than with glass ionomer (GI) cements 70,71) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the reduction in bond strength values when push-out testing was used, it was caused by internal stresses at the dentin-post interface 72) . On the influence of luting agents upon retentive strength, Table 3 also shows that zirconia posts bonded to teeth with resin cements exhibited higher retentive strengths than with glass ionomer (GI) cements 70,71) .…”
Section: Resultsmentioning
confidence: 99%
“…2. Retentive strength of zirconia posts The retentive strength of zirconia posts was examined using natural teeth in 11 studies 63,65,66,[70][71][72][73]77,[80][81][82] (Table 3) and in artificial post spaces using different luting agents in five studies 68,[74][75][76]79) (Table 4). The bond strength of zirconia posts to different core materials was also examined in six studies 64,67,69,78,81,83) (Table 5), thus making it a total of 21 studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, in resin cementation, the possibility of fracture of the restoration and the supportive tooth is decreased compared to the conventional bisphenol-A-glycidyl dimethacrylate (Bis-GMA) containing cements. Therefore, many investigators recommended the usage of adhesive resin-based cement in the regions where adhesion is important because of the strong occlusal forces (10,(31)(32)(33)(34). In their study which focused on alumina disks infiltrated with glass, Kern and Thompson (35), have reported that the adhesive resistance of samples cemented with Bis-GMA composite resin had lower bond strength than the samples bonded with MDP-containing composite resin.…”
Section: Discussionmentioning
confidence: 99%
“…Resinous cements have stronger tensile and shear bond strengths to zirconia than other cement types, making them the preferred choice for clinical use . However, several bond strength studies have reported that adhesive failures have occurred at the resin/zirconia interface, rather than at the cement/dentin interface .…”
mentioning
confidence: 99%